2020
DOI: 10.1051/e3sconf/202014703025
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Nanoparticles Chitosan from Crustaceans Shell Using the Top-down Method

Abstract: Research on the manufacture of nanoparticles of chitosan through top-down method has a limited publication. Most of the research on chitosan nanoparticles was conducted by ionic gelation and other methods. Therefore, this study aimed to investigate the characteristics of nanoparticles chitosan through top-down method. The rprocedure was composed using High Energy Milling (HEM) with different sizes of ball and milling time. The responses observed from this research were particle sizes, yield, viscosity and zeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Chitosan nanoparticles (Cs-NP), colloidal solid particles ranging from 1 to 1000 nm, have piqued the interest of researchers due to their nano size, wide surface area, biodegradability, and remarkable biocompatibility [21]. These characteristics contributed to their high adsorption potential and reactivity, which are both beneficial for extracting heavy metal ions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan nanoparticles (Cs-NP), colloidal solid particles ranging from 1 to 1000 nm, have piqued the interest of researchers due to their nano size, wide surface area, biodegradability, and remarkable biocompatibility [21]. These characteristics contributed to their high adsorption potential and reactivity, which are both beneficial for extracting heavy metal ions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several specific techniques are employed for the fabrication of chitosan-based biogenic nanoparticles, each offering distinct advantages in terms of control over nanoparticle properties and scalability. Because they are more stable and have a higher adsorption capacity and better transport capability, chitosan nanoparticles enhance the benefits of chitosan 29 . The past several decades has seen the use of a variety of techniques, including ionic gelation, microemulsions, emulsification, cross-linking, and polymerization, to generate chitosan nanoparticles.…”
Section: Synthesis Methods For Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…The chitosan particle size and molecular structure produced by this approach vary depending on some changes in the procedure. 300 nm to 500 nm is typically the range of findings from such procedures 29 . The synthesis of nanoparticles via biogenesis is favoured over chemical or physical methods because it is a less time-consuming, safe, environmentally benign, economically and energetically feasible process that maximises the redox potential of metabolites produced by biological entities to transform macromolecules into nano form 30 .…”
Section: Synthesis Methods For Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…The algorithm processed the image of cluster 2 (holes) a median filtering stage, of 5 × 5 pixels mask, eliminates the small pixels (salt and pepper) and a binarization step using OTSU method to adapt the threshold according to the image [51] is necessary. Finally, the regions (holes) were extracted.…”
Section: Median Filter and Binarizationmentioning
confidence: 99%
“…ζ-potential of the novel films ranged from 8.92 mV in Chitosan to 45.9 mV in Chitosan/Silica Nanoparticle/N films, respectively, Figure 5a. Syamdidi et al, [51] reported that nanoparticles with a ζ-potential above 40 mV can present a stable suspension as the surface loads may prevent aggregations among particles. The reasonably stable ζ-potential values could be due to the presence of nisin that take a part in reducing the tension between solid-liquid surfaces and blocks the aggregations between particles.…”
Section: Physical-chemical Characteristicsmentioning
confidence: 99%